Evaluasi Tingkat Kesesuaian Penyimpanan Obat Di Gudang Farmasi Rsud Prof. Dr. Ma Hanafiah Sm Batusangkar - Novrita, Sisri; Rilisa, Berti Wila; Reslina3, Isra (Jurnal Ilmu Kesehatan Abdurrab, 2024)
Drug management is an important aspect in improving the quality of hospital services, to support the smooth process of pharmaceutical services and to ensure the quality of pharmaceutical preparations. Hospital service standards include clinical pharmacy service standards and drug management. The purpose of this study was to see whether drug storage in the Prof.Dr.MA Hanafiah SM Batusangkar Hospital warehouse complies with the storage indicators of Permenkes No. 72 of 2016. This research was conducted from February to May in the pharmacy warehouse at Prof.Dr.MA Hanafiah SM Batusangkar Hospital. This research is a non-experimental descriptive research with data collection methods used are interviews and observations based on the standards of the RI Minister of Health No. 72 of 2016 and documentation. Based on the results of the study, it was found that the level of suitability of storage in the pharmaceutical installation warehouse at Prof. Dr. MA Hanafiah SM Batusangkar Hospital was 89% in accordance with Permenkes No 72 of 2016. Meanwhile, logistics management was fairly good with a percentage of conformity of drugs with stock cards of 100%, there were no damaged drugs but there was a percentage of 0,037% expired drugs.